Disordered eating behaviors in female physique athletes - Whitehead, J.; Slater, G.; Wright, H.; Martin, L.; O`Connor, H.; Mitchell, L. (European Journal of Sport Science, 2020)
Despite substantial growth in participation rates in physique sports, little is known about the modern day female physique athlete. The extreme physique traits of successful female physique athletes suggest this population may be particularly at risk of developing disordered eating (DE). The aim of this study was to determine if female physique athletes across the main divisions of bikini, fitness, figure and bodybuilding were at risk of DE and to explore possible associated risk factors. Furthermore, we aimed to investigate differences in incidence of DE across divisions given differences in physique requirements. Female physique athletes (n?=?348) were recruited using targeted methods and completed an online survey based on validated questionnaires, including the Drive for Thinness, Body Dissatisfaction, and Bulimia subscales of the Eating Disorder Inventory (EDI), Pathogenic Weight Control Measures (PWCM), and the Cognitive Dietary Restraint subscale of the Three-Factor Eating Questionnaire (TFEQ-CDR). Athletes scoring above the cut off values for one or more of the EDI subscales or engaged in at least one of the most concerning PWCM (binge eating, laxative use, and self-induced vomiting) were considered at risk of DE. Approximately half of the participants were identified with DE (46.6%), independent of division, with 27.3% exhibiting clinical and 19.3% having subclinical DE. Furthermore, approximately half (48.9%) of participants engaged in at least one of the most concerning PWCM within the past three months, with a smaller proportion (5.2%) engaging in all three PWCM. Weak but significant correlations were found between some EDI subscales and reason for sport participation, BMI and body composition goals. Drive for thinness and body dissatisfaction were positively associated with use of PWCM. In conclusion, a high proportion of female physique athletes were identified with DE, with a concerning number of athletes engaging in harmful PWCM.